Charlotte Kerners Roman "Blueprint. Blaupause" und seine filmische Adaption - Zum Potenzial der Innenweltdarstellung in Buch und Film = Charlotte Kerner`s novel "Blueprint. Blaupause" and its film adaption - the potential of the inner world view in the book and film - Ratajczak, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article attempts to compare Charlotte Kerner`s novel under the title "Blueprint. Blaupause" andits film version, directed by Rolf Schübel, looking at ways and means of showing the inner lives ofcharacters. First, there follows an analysis of the realization of this objective in the text, carried outby means of modern narratological categories (type of narrator, his position, way of telling, etc.).
Keywords: Kerner, Charlotte (niemiecka pisarka; 1950- ); adaptacja filmowa